Comparative Analysis of Water Management Practices in Denmark, Egypt and Uganda: Implications for Sustainable Water Management in Uganda - Ashaba, Junior Twehamye (AUC Knowledge Fountain, 2025)
Water scarcity and mismanagement are escalating global challenges, with over two billion people lacking access to safe drinking water and projections indicating that nearly two thirds of the world’s population could face water shortages by 2050 (Jones et al., 2024). This thesis presents an analysis of water governance and management practices in Denmark, Egypt, and Uganda-three countries that exemplify diverse hydro-climatic conditions, socioeconomic realities, and institutional frameworks. The study explains how governance structures, technological innovation, stakeholder participation, and policy design shape water resource outcomes, and how lessons from Denmark and Egypt can inform more resilient and sustainable water management in Uganda. Employing a mixed-methods approach, the research integrates quantitative and qualitative survey data from 78 respondents and qualitative insights from 27 in-depth interviews with policymakers, technocrats and community beneficiaries. The analysis is structured on six thematic axes: Integrated Water Resources Management (IWRM), climate change adaptation, technology and innovation, environmental sustainability, community participation and transparency, and international cooperation. The findings demonstrate how Denmark’s decentralized, prevention-focused model showcases high public trust, advanced technology adoption, and robust stakeholder engagement; while Egypt’s centralized, Nile-dependent system demonstrates the complexities of transboundary resource management and the critical role of agricultural modernization. Uganda’s decentralized approach, though progressive in policy, faces significant policy implementation barriers due to limited resources, weak institutional capacity, and insufficient stakeholder engagement. Key findings reveal that Denmark excels in sector integration, funding and participatory governance; while Egypt demonstrates adaptability through strategic planning and international collaboration but struggles with rural accessibility and environmental pressures. Uganda’s challenges are rooted in limited funding, fragmented governance and insufficient technological capacity resulting in persistent gaps in service delivery and climate adaptation. The thesis proposes that effective water governance requires context-sensitive solutions, strong institutional foundations, and genuine community ownership. By adapting proven strategies from Denmark and Egypt, including robust regulatory frameworks, integrated planning, and participatory mechanisms, Uganda can advance toward more equitable and sustainable water management. This research highlights that cross-country policy learning, tailored to local realities, is vital for building resilient water governance systems capable of addressing current and future challenges.